Studies on the three cysteines of mouse glutathione s-transferase P1 - McManus, Gavin (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2006)
The present study has identified the "alkahne thiol" of mGSTP1 originally described by Phillips and Mantle (1993) as cystein e-169. In addition cysteine-47 is confirmed as the reactive "neutral" pK thiol. Cysteine-14 in the C14* mutant is unreactive at neutral pH and only slowly reacts under alkaline conditions. Several key experiments however suggest that Cys-14 can form a disulphide with Cys-47 and this may occur under conditions when the basic dimeric structure is maintained. A comparison of the extent of reaction of DTNB with GSTP1 forms with only Cys-14 or only Cys-47 sum to a significantly lower value than obtained when both Cys-14 and Cys-47 are present. A simple mechanism to explain this is has been presented where an initial mixed disulphide between NTB and Cys-47 destabilises the α2-loop allowing Cys-14 to attack the modified Cys-47 forming a stable disulphide between Cys-14 and Cys-47 and releasing NTB. Whether this thioredoxin like half reaction has any functional significance is presently unclear, how ever it should be noted that treatment of C169A with relatively low concentrations of H2O2 resulted in the formation of the Cys-14/Cys-47 disulphide as revealed by a species running with an apparent mobility of 20kDa on SDS/PAGE in the absence of any mercaptoethanol.
Keywords: Biochemistry and Immunology, Ph.D.; Ph.D. Trinity College Dublin